Spatial–Institutional Configurations of Community-Based Production Cooperatives: Evidence from Two Urban Kampungs in Indonesia - Prajnawrdhi, Tri Anggraini; Milani, Fanisa Dwi Aulia; Mahira, Eka Diana; Septanti, Dewi; Setyawan, Wahyu (RUAS, 2026)
This study examines the spatial-institutional configurations of community-based production cooperatives in two dense urban kampungs, Kampung Penjahit (Denpasar) and Kampung Lontong (Surabaya), and their implications for architectural and urban design discourse. A comparative qualitative–quantitative case study was conducted, integrating non-participant observation, in-depth interviews, 1–5 scale perception questionnaires, settlement morphology mapping, and dwelling typological diagramming. Qualitative data were thematically coded in NVivo 15, while perception data were analysed using the Kruskal–Wallis test in SPSS. Findings reveal two contrasting configurations. Kampung Lontong displays a cooperative-mediated model characterised by compact-clustered morphology, with the cooperative functioning as an institutional-spatial anchor, an alley network operating as a production corridor, and productive social capital. Kampung Penjahit displays an individuated production model marked by linear-dispersed morphology, autonomous dwelling-as-workshop units, and a religious association performing only a symbolic role; nevertheless, residents exhibit higher work discipline and superior arterial-road and parking access. The spatial-institutional configuration framework serves as a typological example for the design of inclusive productive villages in dense Southeast Asian cities.